Non-humans in Amerindian South America : ethnographies of indigenous cosmologies, rituals and songs - Rivera Andía, Juan Javier (EASA series, 2022)
"Drawing on fieldwork from diverse Amerindian societies whose lives and worlds are undergoing processes of transformation, adaptation, and deterioration, this volume offers new insights into the indigenous constitutions of humanity, personhood, and environment characteristic of the South American highlands and lowlands. The resulting ethnographies - depicting non-human entities emerging in ritual, oral tradition, cosmology, shamanism and music - explore the conditions and effects of unequally ranked life forms, increased extraction of resources, continuous migration to urban centers, and the (usually) forced incorporation of current expressions of modernity into indigenous societies"--